1963
DOI: 10.1083/jcb.18.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth in Rat Enamel

Abstract: Observations have been made, using electron microscopy and x-ray diffraction, on the changes in crystal size and shape which occur in developing rodent enamel during mineralization. Small enamel pieces isolated from ground sections of rat molars and incisors were either embedded in methacrylate and sectioned with a diamond knife for electron microscopy, or they were mounted intact on glass fibers in a Debye-Sherrer type powder camera for x-ray diffraction. By either approach it was found that the apatite cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
103
1

Year Published

1965
1965
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(113 citation statements)
references
References 11 publications
9
103
1
Order By: Relevance
“…Needlelike enamel rods might be tens of microns long (up to 100 lm) but sometimes only 50 nm wide and 30 nm thick (Fig. 15 bottom; Avery 2001; Nanci 2012; Jandt 2006; Chen et al 2004;Rönnholm 1962;Nylen et al 1963;Miake et al 1993;Daculsi et al 1984;Jodaikin et al 1984;Bres and Hutchison 2002). They are quite different from the much smaller crystals of dentine and bone (Table 3), but all of them consist of biological apatite (Schroeder and Frank 1985;Brès et al 1990).…”
Section: Teethmentioning
confidence: 99%
See 2 more Smart Citations
“…Needlelike enamel rods might be tens of microns long (up to 100 lm) but sometimes only 50 nm wide and 30 nm thick (Fig. 15 bottom; Avery 2001; Nanci 2012; Jandt 2006; Chen et al 2004;Rönnholm 1962;Nylen et al 1963;Miake et al 1993;Daculsi et al 1984;Jodaikin et al 1984;Bres and Hutchison 2002). They are quite different from the much smaller crystals of dentine and bone (Table 3), but all of them consist of biological apatite (Schroeder and Frank 1985;Brès et al 1990).…”
Section: Teethmentioning
confidence: 99%
“…The first detectable crystals in enamel formation are flat thin ribbons (Rönnholm 1962;Nylen et al 1963;Miake et al 1993) that were reported to be OCP (Brown and Chow 1976;Simmer and Fincham 1995;Diekwisch et al 1995;Aoba 1996), b-(Ca,Mg) 3 (PO 4 ) 2 (Diekwisch et al 1995), DCPD (Rey et al 1995a;Bonar et al 1991) or ACP (Beniash et al 2009). The formation process of enamel is different from that for bone or dentine: amelogenin being hydrophobic self-assembles into nano-sized spheres that guide the growth of the ribbon-like dental enamel crystals.…”
Section: Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the integrity of an epithelial layer is subject to continual challenge from both mechanical and biochemical stimuli. Gudipaty et al 1 reveal on page 118 how physical forces can control cell division to aid the maintenance of epitheliallayer integrity.…”
Section: H O R Ac I O D E S P I N O S a And R A Fa E L S O L E R -C Rmentioning
confidence: 99%
“…T ooth enamel combines hardness and impact resistance 1,2 , making it extremely durable -which is essential to the lifelong survival of toothed organisms, because most animals cannot replace their adult teeth. On page 95, Yeom et al 3 report a tooth-enamel-inspired composite material in which a columnar architecture of hard constituents is interlaced with a soft polymer matrix.…”
Section: H O R Ac I O D E S P I N O S a And R A Fa E L S O L E R -C Rmentioning
confidence: 99%